“Economic Miracle” in France: Formation and Results of the Dirigisme Model in 1944–1973 - A. G. Khudokormov (Мир новой экономики, 2019)
The purpose of the article is to show the determining role of dirigisme in the restoration and prosperity of France in the period 1944–1973; the influence of nationalization of enterprises of leading industries, banks on a compensatory basis; indicative planning for the revival of the country’s economy and achieving high rates of its growth; the rise of agriculture; the formation of a unified system of state social insurance. As a result of the reforms carried out in the 1950s and 1960s, these decades were a period of accelerated and almost continuous growth of the French economy. The ‘engines’ of economic growth were heavy industries, which accounted for the majority of all investment in the industry. The equipment in machine building (first of all in the car and aircraft construction, production of machines and devices) was updated; metallurgy, electrical engineering, chemistry, oil refining were modernised; the nuclear industry was created for the first time in the history. At the same time, in agriculture was held large-scale mechanisation. All this was accompanied by significant positive changes in the social sphere: soon after the end of WWII, the 40-hour working week was restored, annual leave for workers and employees was returned. Already by 1946, a unified state social insurance system was formed, which extended to all categories of employees, except for workers in the agricultural sector. As a result, the dirigisme model in France in the period 1944–1973 allowed this country not only to restore the war-ravaged economy, and also to achieve impressive success in industry, agriculture and the social sphere, to return it to one of the key positions in the world. It leads to the conclusion that the experience of using the conductor model in France can be used in the development of areas of reform of the Russian economy in current conditions.